2005
DOI: 10.1002/anie.200501678
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Organic Alloys Based on Organic Layered Crystals

Abstract: Random layer: Multicomponent organic solid solutions were obtained by treating equimolar mixtures of two or more aliphatic carboxylic acids with 1‐naphthylmethylamine (NMA; see scheme). The single sharp XRD peaks of the crystalline products indicate specific pairing of alkyl groups between the NMA layers to form mixed crystals rather than eutectic mixtures of the components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
33
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 72 publications
(7 reference statements)
1
33
0
Order By: Relevance
“…Recently, we demonstrated that some mixtures of 1-naphthylmethylammonium n-alkanoates with various lengths of the alkyl groups provided binary and higher-order multicomponent molecular alloys that are single-phase crystalline materials composed of all the components (Figure 1). 3 Moreover, in a series of the binary mixtures, the mixtures with pairs of salts (i and j) 4,5 with different lengths of alkyl chains ( j ¹ i > 6) provided eutectic mixtures…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we demonstrated that some mixtures of 1-naphthylmethylammonium n-alkanoates with various lengths of the alkyl groups provided binary and higher-order multicomponent molecular alloys that are single-phase crystalline materials composed of all the components (Figure 1). 3 Moreover, in a series of the binary mixtures, the mixtures with pairs of salts (i and j) 4,5 with different lengths of alkyl chains ( j ¹ i > 6) provided eutectic mixtures…”
mentioning
confidence: 99%
“…One was constant against k and the other was shifted to lower 2ª with increase of k. In order to prepare all other possible patterns summarized in Figure 2, the four salts i, j, k, and l, were properly selected, according to the rule for the formation of the binary organic alloys. 3 For type (2), three salts with the successive numbers of methylene groups (i, j = i + 1, k = i + 2) and one salt that had six methylenes longer than that of the largest number among the other three (l > k + 6) were chosen. Figure 5a shows the XRD patterns of the mixture from the four salts; 4, 5, 6, and 19.…”
mentioning
confidence: 99%
“…However, this has only been possible where the molecules concerned are very similar in size, shape, and nature. [1,3,4] Herein we report a new approach to the preparation of crystals from continuously variable mixtures of organic molecules. The strategy allows the incorporation of multiple and diverse units, including molecules which may not crystallize by themselves.…”
mentioning
confidence: 99%
“…[1,2] However for organic molecular crystals, with diverse structures governed by weak intermolecular forces, such exchanges are more problematic. There are some examples where solid solutions ("organic alloys") [3] are formed from molecules which can be mixed in any ratio within the same crystal structure. However, this has only been possible where the molecules concerned are very similar in size, shape, and nature.…”
mentioning
confidence: 99%
See 1 more Smart Citation